Expecting to teach promotes motor learning of a golf putting task in children - Salehi, Mohammad; Saemi, Esmaeel; Doustan, Mohammadreza (Akademia Wychowania Fizycznego w Poznaniu)
Introduction. Researchers have shown that the learners achieve higher levels of learning when they learn with the aim and expectation of teaching their content to others. Recently some motor behavior researchers have also examined this learning method, and have indicated that expecting to teach others improves motor learning in adults. The purpose of the present study was to examine the effect of expecting to teach others on the learning of a golf-putting task in children. Material and Methods. Participants consisted of 24 children (all males; Mage = 9.58; SD = 0.50 years) who were randomly assigned into two experimental groups. Participants in the group expecting to teach others were instructed as follows: “given that you have to teach golf putting to some people the day after the acquisition phase, you have the opportunity to practice this skill carefully today and tomorrow”. Participants in the group expecting to be tested received the following instructions; “you have the opportunity to practice this skill carefully today and tomorrow expecting to be tested in this skill”. Results. The results showed that the children in the group expecting to teach others had better accuracy scores relative to children in the group expecting to be tested in the retention phase (p ≤ 0.05). Conclusions. The findings of this study suggest that promoting the expectation to teach others would improve motor learning in children.
Keywords: expecting to teach; golf putting task; motor learning; children